Left main stenting with stent dislodgement and entrapment in the common femoral artery: a successful transcatheter stent retrieval - Egbuche, Obiora (Am J Cardiovasc Dis, 2021)
Proximal left main stenting in symptomatic patients with flow-limiting stenosis is an alternative revascularization strategy in individuals with low syntax score and high operative risk. Stent dislodgement is associated with adverse cardiovascular events and retrieval of fully deployed stents is generally prohibited as it increases the risk of severe complications. Stent dislodgement and entrapment in the femoral vascular system occur infrequently during percutaneous coronary interventions. In this report, we illustrate a prompt and safe transcatheter technique to successfully retrieve an expanded and dislodged coronary stent entrapped in the common femoral artery without need for a more invasive surgical approach.